Enhanced ferroelectric property of P(VDF-TrFE-CTFE) film using room temperature crystallization for high-performance ferroelectric device applications - Cho, Y; Ahn, D; Park, J; Pak, S; Lee, S; Jun, B; Hong, J; Lee, S; Jang, J; Hong, J; Morris, S; Sohn, J; et al. (Wiley, 2016)
The ferroelectric β-phase in a poly(vinylidenefluoride-trifluoroethylene-chlorotrifluoroethylene) film is successfully formed using a room temperature solvent-annealing process and shows enhanced ferroelectricity compared to a thermally annealed film. Applications in electronics and energy are demonstrated with significantly enhanced device performances for a solvent annealing (SA) film employed devices compared to a thermal annealing film employed due to enhanced ferroelectricity of the SA film.